Mechanical and electrical properties of carbon nanotubes surface‐stamped on polydimethylsiloxane for microvalve actuation. Issue 4 (6th August 2012) - Salzbrenner, Jeffrey; Apblett, Christopher; Khraishi, Tariq
Abstract We report a study of the electrical and mechanical effects of the inclusion of a thin layer of multiwalled carbon nanotubes (MWCNTs) into the surface of polydimethylsiloxane (PDMS) as a method of creating an electrically actuated, flexible microfluidic valve. Samples of PDMS with various surface loadings of MWCNTs were prepared and tested using a uniaxial tension tester, combined with a four‐point probe electrical test. In contrast to other works reporting the inclusion of MWCNTs in the bulk of the material, we have found that inclusion of the MWCNTs on the surface only has no discernible effect on the mechanical properties of the PDMS samples, but causes a significant and repeatable change in the electrical performance. We have found that a loading of 4.16 g m−2 results in an electrical resistivity of 7.31 × 10−4 Ω cm, which is 200% lower than that previously reported for bulk inclusion samples. The microstructure of the MWCNTs was found to consist of both individual fibers and spherical clumps of fibers. We suggest that, due to the microstructure of the MWCNTs used in this study, the mechanical properties can be modeled as a thin layer of particulates, while the electrical properties can be modeled as a thin bed of bulk MWCNTs. © 2012 Society of Chemical Industry